E-080 Acquisition of DWI burden in early subarachnoid hemorrhage. (22nd July 2018) - Kayan, Y; Almandoz, J Delgado; Fease, J; Wallace, A; Scholz, J; Milner, A; Banerji, N; Mulder, M
Abstract : Purpose: To determine the natural history of diffusion weighted imaging (DWI) abnormalities in early acute subarachnoid hemorrhage (SAH). Methods: Patients with diffuse SAH at our institution were offered enrollment in a prospective study in which serial MRI, including DWI, FLAIR, PWI, and ASL sequences, was performed at admission, 7 days, 30 days, and upon the development of signs/symptoms of vasospasm. Patient demographics, Hunt-Hess grade, modified Fisher score, and underlying lesion and treatment technique were recorded. Results: Between November 2013 and August 2017, 50 patients were enrolled, 37 women, mean age 58, 20 current smokers. Hunt-Hess grade mean was 3.0. Modified Fisher score mean was 3.5. All underlying vascular lesions were treated endovascularly: 17 ACA aneurysms, 14 ICA aneurysms (including PCOM), 10 MCA aneurysms, 3 basilar tip aneurysms, 1 vertebral aneurysm, 1 posterior fossa AVM, and 4 angiographically-negative SAHs. 31 patients (62%) had DWI abnormalities on their admission scan; all had undergone a catheter angiogram or endovascular treatment of the underlying lesion prior to the MRI. The total number of DWI abnormalities amongst these patients was 250 (214<5 mm, 22 5–9 mm, and 14≥10 mm). 70 were FLAIR hyper-intense. 28 lesions were within non-catheterized vascular territories. At 7 days, the total number of DWI abnormalities was 267 (224<5 mm, 27 5–9 mm, 16≥10 mm), 100 FLAIR hyper-intense, 19 within non-catheterized vascular territories. 11 patients (22%) had an increase in the total number of DWI abnormalities without additional intervention. Of these, 2 patients (4%) had an increase in the number of DWI abnormalities outside of the territory of the treated lesion. Only 1 patient had a perfusion abnormality; this patient did not incur an increase in DWI burden. Conclusion: The acquisition of additional multifocal ischemic injury to the brain is common in early SAH. This phenomenon is independent of cerebral perfusion and large-vessel vasospasm. Disclosures: Y. Kayan: 2; C; Medtronic, Penumbra. J. Delgado Almandoz: 2; C; Medtronic, MicroVention, Penumbra. J. Fease: None. A. Wallace: None. J. Scholz: None. A. Milner: None. N. Banerji: None. M. Mulder: None.